The semantic change of positive vs. negative adjectives in Modern English - Altakhaineh, Abdel Rahman Mitib (Lingua Posnaniensis, 2018)
This study examines two types of semantic change, namely amelioration and pejoration, through comparing the positive/negative senses of 20 English adjectives over time in the Oxford English Dictionary (OED). It also aims to explore whether the semantic change, which may have occurred in these words, can be associated with their frequency in The British National Corpus (BNC). The results reveal that the stability of the target adjectives has indeed changed over time. The positive adjectives were originally somewhat negative, neutral or positive, and then started to become positive if they were previously negative or neutral if they were previously positive. Conversely, the negative adjectives tend to become less negative over time. The study suggests that the semantic change of these adjectives could have been motivated by a tendency to reduce lexical complexity, which speakers may have done for pragmatic reasons, such as successful communication. The study also proposes that the semantic change could also be related with the frequency of the adjectives undergoing the change. The study concludes with recommendations for further research.